ANALISA KINERJA BUS RAPID TRANSIT (BRT) TRANS SEMARANG KORIDOR II TERMINAL TERBOYO-TERMINAL SISEMUT - Agnesia Putri Kurnianingtyas; A`izzatul Mardliyah; Kiki Lana Fauzizah (Indonesian Journal of Spatial Planning, 2020)
Semarang as one of the big cities in Central Java has provided public transportation which is Bus Rapid Transit (BRT) as an effort to reduce congestion and the use of private transpotation. There are eight main corridor and one special corridor that are provides until 2021, one of them is Corridor II with Terboyo-Sisemut Route. This study is aim to analyze the servce performance of Corridor II with the optimalization the use of BRT in this route, find the problem factors that influence and formulate the step for quality services improvement. The method of this study is quantitative method by calculating the weight value through assessment indicators based on the standards of the Director General of Transportation. These indicators are obtained from the results of dynamic surveys and static surveys. From the analysis, the service performance of BRT Corridor II at Terminal Terboyo-Sisemut PP is in good category. The number of fleets needed in corridor II is 21 units. Based on the results of the evaluation, one recommendation to improve the quality service of BRT is to make a special lane for BRT to make travel time faster, so that users are more interested in using BRT.